STUDI KRITIS UNDANG UNDANG NOMOR 1 TAHUN 1974 DAN PENERAPANNYA DI MASYARAKAT - Maftuhah, Imat (Universitas Mathla’ul Anwar Banten, 2025)
The law is one of the device that have a role is very important, to create the country which saved and controlled, as the law of country, Indonesia has a variety of the law ranging from the law unwritten or called with the law of indigenous as well as the law written is called the law of reserved, for the country such as Indonesia is absolute the law of marriage as well as accommodate the principles and has given the base of marriage law that has been become a grip and has been true for a variety of community and society. According with the base of philosophy’s pancasila and legislation laws of basic 1945, than the law is on the law parties should be able to bring into reality principles, contained in pancasila and legislation laws of basic 1945, while on the other parties also have to accommodate all of the fact which lives in the society now.